Rede proprietária das maiores corporações brasileiras: centralidade, intermediação e grupos - Cruz, Wilton Vicente Gonçalves da (2021)
The question of who controls modern corporations is one of the most lasting of the social sciences. Ownership is one of the forms that control is exercised. Ownership networks enable to understand who are the controllers of assets, shares, and strategic decisions. There is a lack of studies using network analysis for the study of control in the Brazilian corporate sector. By this, this work aims to answer the question of who are the owners of the largest Brazilian corporations. To fill this lack, the objectives of this work are: 1) Analyze measures of density, middle-degree, modularity, and the number of connected components; 2) Analyze centrality measures of weighted out-degree, betweenness, and eigenvector; 3) Identify and analyze communities from measures of modularity class. This research is exploratory, uses analysis of content and documental analysis of quantitative data. A sample of 122 Brazilian corporations was used. A network with 1828 nodes and 3253 ownership links was constructed. The measures calculated were at network-level, node-level centrality, communities, and control flow. The results show that the network is low density, is sparse, and highly modularized. The centrality measures reveal that financial firms (mainly passive investment funds) and corporations linked to the Brazilian state have the highest values. Regarding community detection, were identified large groups of multinationals, financial firms, and firms linked to the Brazilian state and these communities have the highest values of control flow. This configuration converges to a hierarchical form of capitalism. From these results, is possible to infer financialization of the control of the largest Brazilian corporations and also the force of the state in key sectors of the economy. The consideration of other forms of corporate control (as board-interlocking and cross- shareholders) and a temporal analysis are suggestions for this sequence of this research.